2008
DOI: 10.1007/s00216-008-2012-1
|View full text |Cite
|
Sign up to set email alerts
|

An artificial virus-like nano carrier system: enhanced endosomal escape of nanoparticles via synergistic action of pH-sensitive fusogenic peptide derivatives

Abstract: We previously reported that transferrin (Tf)-modified liposomes (Tf-L) additionally modified with a cholesterylated pH-sensitive fusogenic peptide (Chol-GALA) can release an encapsulated aqueous phase marker to cytosol via endosomal membrane fusion. However, further obstacles need to be overcome to bring the Tf-L to the level of a viral-like gene delivery system. In this study, we developed a novel packaging method to encapsulate condensed plasmid DNA into PEgylated Tf-L (Tf-PEG-L) to form a core-shell-type na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 27 publications
0
73
1
3
Order By: Relevance
“…Other studies showed that the attachment of Tf to the surface of liposomes with a PEG spacer (Tf-PEG-Lip) enhances cellular uptake efficiency and speed, compared with liposomes modified with Tf, albeit without the PEG spacer [14]. However, the effect of the topology of the ligand on the internalization mechanism is still unknown in arginine-rich peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that the attachment of Tf to the surface of liposomes with a PEG spacer (Tf-PEG-Lip) enhances cellular uptake efficiency and speed, compared with liposomes modified with Tf, albeit without the PEG spacer [14]. However, the effect of the topology of the ligand on the internalization mechanism is still unknown in arginine-rich peptides.…”
Section: Introductionmentioning
confidence: 99%
“…1, which was presumably due to an increase in endosomal escape by virtue of the function of GALA after the R8/GALA-MEND was taken up via endocytosis. 11,12) No further enhancement in activity was observed Ͼ2 mol%, because the ability of GALA to accelerate the endosomal escape might reach the limit in this formulation. Furthermore, in the case of 4 mol% of Chol-GALA, the aggregation occurred occasionally in R8/GALA-MEND formulation, which could have been caused by fusion between the lipid envelope of the MEND due to an excess amount of GALA.…”
Section: Resultsmentioning
confidence: 91%
“…Cholesterol-GALA, which inserted in the liposome membrane, and PEGylated GALA, constituting the outer shell, were used to induce interaction and fusion between liposomes and endosome membranes. [23] Due to its negative charge, (9 of 26) 1700022 GALA is not able to bind electrostatically plasmid DNA or oligonucleotides. However, by replacing several of the negatively charged glutamic acid residues by positively charged lysine amino acids, Szoka and co-workers prepared a peptide that is referred to as KALA and which combines membrane-disrupting activity with the ability to form polyplexes with DNA and oligonucleotides.…”
Section: Endosomal Disruptionmentioning
confidence: 99%
“…[16,17] Targeting the human epidermal growth factor receptor-2 via the monoclonal antibody Trastuzumab has been reported to facilitate breast cancer cellular internalization of block copolymer micelle-based nanoparticles as well as polyplexes. [18,19] Upregulation of the transferrin receptor in pancreas, colon, lung, and bladder cancers was also exploited using transferrin-nanoparticle and linear polymer conjugates, [20][21][22][23] as well as transferrin-modified polyplexes. [24] Another example of a ligand used for prostate and lung cancer targeting is anisamide, which binds to the overexpressed sigma receptor.…”
Section: Introductionmentioning
confidence: 99%